(untitled) (Oratio Directa, 2025)
This study examines declining engagement with formal journalism among Generation Z and its implications for critical thinking in digital information environments. It uses a descriptive qualitative reading of contemporary media practices supported by literature on journalism as a social institution, uses and gratifications, media literacy, critical thinking, and digital culture. The analysis identifies a shift in the meaning of news: virality increasingly competes with institutional credibility as a marker of legitimacy. Algorithmically curated social-media feeds encourage rapid and surface-level information processing, filter bubbles, and limited exposure to contrasting perspectives. In-depth journalistic content, by contrast, offers verification, context, structured argument, and opportunities to compare sources. Because the source does not report participant recruitment, sample size, interviews, or coding procedures, comparisons between audience groups are treated as analytical propositions rather than direct empirical effects. The study concludes that declining engagement with formal journalism reflects a broader transformation of information culture and presents a challenge to critical literacy and democratic participation.